Computational Logic in Multi-Agent Systems 11th International Workshop, CLIMAX XI, Lisbon, Portugal, August 16-17, 2010, Proceedings - Dix, Jürgen; Leite, Joao; Governatori, Guido; Jamroga, Wojtek (Lecture Notes in Artificial Intelligence,, 2010)
This book constitutes the refereed proceedings of the 11th International Workshop on Computational Logic in Multi-Agent Systems, CLIMA-XI, held in Lisbon, Portugal in August 2010. The 14 papers included in this volume were carefully reviewed and selected from 31 submissions. The purpose of the CLIMA workshops is to provide a forum for discussing techniques, based on computational logic, for representing, programming and reasoning about agents and multi-agent systems in a formal way. CLIMA 2010 featured two thematic special sessions on norms and normative multi-agent systems and logics for games and strategic reasoning. .